PENERAPAN PANEL SURYA SEBAGAI MEDIA PEMBELAJARAN ENERGI TERBAHARUKAN DAN ENERGI LISTRIK TAMBAHAN DI SEKOLAH ALAM GAHARU - Istiqomah, Istiqomah; Aziz, Arif Abdul; Rizal, Achmad; Bahrudin, Muhammad Fahriza; Soediponegoro, Soediponegoro; Azriansyah, Azriansyah; Sundawa, Naufal Widad; Isnaini, Abdillah Nur; Antu, Vincentius Adisurya Fransisco (Universitas Muhammadiyah Mataram, 2024)
Abstrak: Sekolah Alam mengedepankan alam sebagai aspek utama objek pembelajaran, sehingga kewajiban menjaga alam menjadi hal penting untuk diajarkan ke peserta didik. Salah satu upaya untuk menjaga alam adalah dengan menggunakan energi baru dan terbarukan sebagai alternatif energi bersih. Sehingga hal tersebut menjadi misi yang sedang digiatkan di Sekolah Alam Gaharu. Pada pelaksanaan kegiatan pengabdian masyarakat ini, tim berusaha memenuhi kebutuhan sekolah alam yaitu penerapan EBT berupa panel surya sebagai media pembelajaran dan energi listrik tambahan untuk kegiatan outdoor di sekolah alam tersebut. EBT yang diterapkan adalah panel surya yang kiranya mudah dirancang menyesuaikan kebutuhan Sekolah Alam Gaharu. Panel surya yang menghasilkan listrik DC diintegrasikan dengan sistem lain seperti Aki dan inventer DC ke AC agar catu daya bisa langsung digunakan perangkat elektronik di Sekolah Alam Gaharu. Diharapkan kegiatan masyarakat ini menjadi media pembelajaran EBT di Sekolah Alam Gaharu. Diakhir kegiatan akan ada survei kepada 15 guru di Sekolah Alam Gaharu untuk melihat keefektifan penerapan panel surya sebagai media pembelajaran di sekolah alam. Dari hasil survei yang dilakukan tersebut disimpulkan 100% kegiatan memenuhi kebutuhan dari Sekolah Alam Gaharu.Abstract: The Nature School prioritizes nature as the main aspect of learning objects, so the obligation to protect nature is an important thing to teach to students. One effort to protect nature is to use new and renewable energy as a clean energy alternative. So this has become a mission that is being carried out at the Gaharu Nature School. In carrying out this community service activity, the team tried to meet the needs of the natural school, namely the application of new renewable energy in the form of solar panels as a learning medium and additional electrical energy for outdoor activities at the natural school. The new renewable energy implemented is solar panels which can be easily designed to suit the needs of the Gaharu Nature School. Solar panels that produce DC electricity are integrated with other systems such as batteries and DC to AC inverters so that the power supply can be directly used by electronic devices at Alam Gaharu School. It is hoped that this community activity will become a medium for new renewable energy learning at Gaharu Nature School. At the end of the activity there will be a survey of 15 teachers at Gaharu Nature School to see the effectiveness of implementing solar panels as a learning medium in natural schools. From the results of the survey conducted, it was concluded that 100% of the activities met the needs of the Gaharu Nature School.